Socially responsible lobbying - Saara Hämäläinen; Sara Yi Zheng (Helsinki Graduate School of Economics, 2023)
Lobbyists are nowadays increasingly involved in promoting businesses through societal investment, producing what has been paraphrased as "corporate beauty contests" due to the uncertain winning criteria. To understand what motivates firm participation in these contests and their effects on welfare, our paper analyzes lobbying contests in which firms can boost their competitiveness in a market for political favors through either monetary contributions or societal investments. We establish that the responsiveness of political favors to social lobbying (i) alleviates lobbying competition, (ii) decreases total lobby spending, and (iii) shifts spending from monetary to social lobbying. This is generally welfare improving. Our results thus suggest that the ongoing transition to societal lobbying is a move toward a more efficient lobbying standard.
Keywords: D43; D83; 330; Lobbying contest; Corporate social responsibility; Beauty contest; Multidimensional expenditure; Differentiation; Endogenous competitiveness; Obfuscation